The benefits of the hazard analysis critical control point (HACCP) system in the fishing industry - Uys, Rolf (Roelof Christiaan Bosenberg) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2000.